PERUBAHAN SOSIAL EKONOMI MASYARAKAT PERDESAAN STUDI TENTANG DAMPAK PERKEBUNAN KELAPA SAWIT TERHADAP AKTIVITAS EKONOMI RAKYAT DI NAGARI KINALI KECAMATAN KINALI KABUPATEN PASAMAN BARAT PROVINSI SUMATERA BARAT - Elfitra Elfitra (Indonesian Journal of Dialectics, 2011)
The development of smallholder’s oil palm plantations rapidly since the last two decades have brought to extensive impact on social change in rural communities in the West Pasaman, mastery pattern changes that result in changes in an increasingly complex social stratification and changes in form and function of social institutions and lifestyles.This research was conducted in Nagari Kinali using the qualitative approach, data collection through observation, interview and documentation study. The focus is the impact of smallholder’s oil palm to changes in social stratification, social institutions and attitudes of rural socioeconomic conditions.The results showed that the presence of smallholder’s oil palm resulted in change of stratification of the people who increasingly prominent and complex patterns of land tenure based on the emergence of rich peasants, small farmers and agricultural laborers. In a social institution widespread changes in family to the nuclear family, work patterns that are of mutual aid to the use of farm workers, kinship-based socialization is replaced by formal education and no longer existense of surau as an educational institution boys.